The Physical Structure of Regional Educational Service Agencies: Implications for Service and Equity Goals - Patrick F. Galvin (Journal of Research in Rural Education, 1995)
One ofthe assumptions underlying the organization and maintenance ofregional educational service agencies, or, educational cooperatives, is that they enable districts to benefitfrom economies ofscale. This study, using datafrom New York state's Board of Cooperative Education Services (BOCES), examines the interaction of district size and wealth factors with BOCES size and wealthfactors as they are related to expenditure levels for service provision. A regression analysis shows that the physical characteristics ofBOCES are significantly related to expenditure levels. ANOVA studies reveal a systematic interaction between district and BOCES characteristics, indicating that the investment levels of similarly structured districts in differently structured BOCES are significantly different. These results suggest that the opportunities available to districts through regional educational service agencies may depend upon their location, afact that violated a basic premise ofschool finance equity.